Polypropylene monoprothesis to correct anterior vaginal wall prolapse with or without urinary incontinence - Paredes Salas, José (2015)
Objectives: To describe the experience with polypropylene monoprothesis use for anterior vaginal wall prolapse repair with or without urinary incontinence. Design: Retrospective, longitudinal, series of cases study. Setting: Hospital Nacional Cayetano Heredia, Lima, Peru. Participants: Patients operated for anterior vaginal wall prolapse. Interventions: All 44 patients operated of anterior vaginal wall prolapse during 2008 consulted for sensation of vaginal bulk and 93,2% for loss of urine. Pelvic organ prolapse quantification (POPQ) determined 93,2% corresponded to III and IV degrees. Main outcome measures: Vaginal prolapse and stress urinary incontinence cure. Results: All 44 patients had surgical treatment of anterior vaginal prolapse with polypropylene mesh and placement of intravaginal posterior sling, 19 (43,2%) with uterine preservation and 25 (56,8%) with vaginal hysterectomy. Immediate complications were 2 hematomas (8%) and 3 vaginal vault infection (12%), both in the vaginal hysterectomy group. Patients reported subjective cure of urine loss and sensation of bulk in all cases evaluated. Conclusions: Polypropylene monoprothesis use can be safe, effective and with less morbidity for anterior vaginal wall prolapsed repair. Nevertheless more studies are needed to establish suitable results at long term.